PERBEDAAN HITUNG JUMLAH TROMBOSIT CARA LANGSUNG DAN BARBARA BROWN (SADT ZONA IV,V,VI dan ZONA V) : (SADT ZONA IV,V,VI dan ZONA V) - Kartika Ikawati Ikawati (Yakpermas Press, 2024)
Direct and Barbara Brown manual platelet counts are the reference methods recommended by ICSH. This manual method is used to confirm if the automatic method can not produce accurate results. Until now there has been no reference that mentions the SADT reading zone for estimating platelet counts. Peripheral blood smear has six zones with different cell distribution and density. The aim of this study was to determine the difference in platelet counts examined using the direct method, Barbara Brown's method of reading zones IV, V, VI and Barbara Brown's reading of zone V. This type of research is analytical observation with a cross-sectional design. The research sample was 30 taken using random sampling technique from the student population of AKKES 17 Agustus 1945 Semarang. The research was conducted in March 2024 at the AKKES Hematology Lab 17 Agustus 1945 Semarang. Counting the number of platelets is done directly by diluting the blood with Rees Ecker's solution into a thoma pipette. The estimation method for calculating the number of platelets (Barbara Brown) is done by calculating the average number of platelets in 10 SADT fields of view and multiplying by a conversion factor of 20.000. . The highest platelet count results were obtained from the Barbara Brown method (SADT zone IV, V, VI) with a mean of 342,470 ± 46,185 cells/(µL), followed by the direct method with a mean of 327,230 ± 50,447 cells/µL and the lowest was the SADT zone V a mean of 319,930 ± 39,172 cells/µL. There was a smaller difference between the direct method and Barabara Brown (SADT zone V). The results of the Anova and Post Hoc tests showed p > 0.05, which means there was no significant difference between the three methods. Keywords: Platelet count; Direct method; Barbara Brown